2022
DOI: 10.1021/acsearthspacechem.2c00002
|View full text |Cite
|
Sign up to set email alerts
|

Riverine Hydrochemical Characteristics of a Typical Karst Urban Watershed: Major Ion Compositions, Sources, Assessment, and Historical Evolution

Abstract: Urban watersheds suffer from great pressure concerning poor water carrying capacity in the karst area with a fragile ecology system and urbanization disturbance. The hydrochemistry of karst urban rivers plays a vital role in the maintenance of water ecology. This study determined the sources of major ions (Na + , K + , Mg 2+ , Ca 2+ , F − , Cl − , NO 3 − , SO 4 2− , and HCO 3 − ) in the Nanming urban watershed. The ion concentrations were dominated by the HCO 3 − -Ca 2+ •Mg 2+ type and complied with the compom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 72 publications
(163 reference statements)
1
14
0
Order By: Relevance
“…Although the YDR was obviously affected by anthropogenic activities, the contribution of natural weathering was critical, especially in the upstream areas. The ratios of Ca 2+ /Na + versus Mg 2+ /Na + and Ca 2+ /Na + versus HCO 3 – /Na + can serve as indicators of mixing lithologies. , These ratios in river waters are inherited from their mineral sources. The silicate end-members used in this study were Ca 2+ /Na + = 0.35 ± 0.15, Mg 2+ /Na + = 0.24 ± 0.15, and HCO 3 – /Na + = 2 ± 0.5, while the carbonate end-members were Ca 2+ /Na + ratios closed to 50, Mg 2+ /Na + ratios close to 10, and HCO 3 – /Na + closed to 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the YDR was obviously affected by anthropogenic activities, the contribution of natural weathering was critical, especially in the upstream areas. The ratios of Ca 2+ /Na + versus Mg 2+ /Na + and Ca 2+ /Na + versus HCO 3 – /Na + can serve as indicators of mixing lithologies. , These ratios in river waters are inherited from their mineral sources. The silicate end-members used in this study were Ca 2+ /Na + = 0.35 ± 0.15, Mg 2+ /Na + = 0.24 ± 0.15, and HCO 3 – /Na + = 2 ± 0.5, while the carbonate end-members were Ca 2+ /Na + ratios closed to 50, Mg 2+ /Na + ratios close to 10, and HCO 3 – /Na + closed to 50 .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the excess solute in river water affected human health through skin absorption, drinking water, and the food chain . At present, NO 3 – and F – have been widely used for the evaluation of non-carcinogenic health hazards. To calculate the HQ index of NO 3 – and F – , the United States Environmental Protection Agency (USEPA) is employed, and details are as follows normalA normalD normalD normali normaln normalg normale normals normalt normali normalo normaln = normalC × normalI normalR × normalE normalF × normalE normalD / ( B W × A Y ) normalH normalQ = normalA normalD normalD / normalR normalf normalD where ADD ingestion is the ingestion intake per day; C is the NO 3 – concentration (mg/L); IR is the daily ingestion rate (0.7 and 1.5 L/d for children and adults, respectively); EF is the frequency of exposure (d/y); ED is the exposure duration (12–25 years); BW is the body weight (16 and 56 kg for children and adults, respectively); and AT is the average time (4380 and 10,950 days for children and adults, respectively). All the data mentioned above are from previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…Probably due to the mixing processes between mainstream of TGR and XBZ, most samples were more close to the river water line of TGR (TRWL, δ 2 H = 8.413 × δ 18 O + 15.782) 36 than GMWL and LMWL. The intense evaporation of river water can also enrich the heavy isotopes in river water and affected the biogeochemical processes of nutrients, 27,53,54 accompanied by a significant decrease in the d-excess value and less than the average value of the GMWL (d-excess = 10‰). 51 Although the d-excess tended to decrease with the increase of δ 18 O in the study area (Figure 4b), the d-excess values of all samples were higher than 10‰, suggesting that the river water experienced slight evaporation.…”
Section: Nitrogen Concentrationsmentioning
confidence: 99%
“…In urban and sub-urban areas, wastewater is one of the main reasons for deteriorating water quality. , Poor-quality irrigation might indeed be the main reason why Afghan agricultural products were rejected from global markets due to the high HM concentrations. , Moreover, it has been reported that children of refugees and immigrants who have recently migrated from Afghanistan to other countries have high blood Pb levels. , It is possible that those affected individuals have been exposed via intake of HM-containing plant edible portions since this is one of the most common pathways for these metals to accumulate in the human body. , In addition, the farmers and other residents of the region are not aware of the harmful effects of HM accumulation in agricultural products originating from irrigation sources.…”
Section: Introductionmentioning
confidence: 99%
“…11 In urban and sub-urban areas, wastewater is one of the main reasons for deteriorating water quality. 16,17 Poor-quality irrigation might indeed be the main reason why Afghan agricultural products were rejected from global markets due to the high HM concentrations. 18,19 Moreover, it has been reported that children of refugees and immigrants who have recently migrated from Afghanistan to other countries have high blood Pb levels.…”
Section: Introductionmentioning
confidence: 99%